Radiocarbon bomb spike reveals biological effects of Antarctic climate change - Laurence Clarke; Robinson, SA; Hua, Q; Ayre, DJ; Fink, D (2012)
The Antarctic has experienced major changes in temperature, wind speed and stratospheric ozone levels during the last 50 years. However, until recently continental Antarctica appeared to be little impacted by climate warming, thus biological changes were predicted to be relatively slow. Detecting the biological effects of Antarctic climate change has been hindered by the paucity of long-term data sets, particularly for organisms that have been exposed to these changes throughout their lives. We show that radiocarbon signals are preserved along shoots of the dominant Antarctic moss flora and use these to determine accurate growth rates over a period of several decades, allowing us to explore the influence of environmental variables on growth and providing a dramatic demonstration of the effects of climate change. We have generated detailed 50-year growth records for C eratodon purpureus and three other Antarctic moss species using the 1960s radiocarbon bomb spike. Our growth rate and stable carbon isotope (δ 13 C) data show that C . purpureus ’ growth rates are correlated with key climatic variables, and furthermore that the observed effects of climate variation on growth are mediated through changes in water availability. Our results indicate the timing and balance between warming, high-wind speeds and elevated UV fluxes may determine the fate of these mosses and the associated communities that form oases of Antarctic biodiversity.